Legal aspects of ownership in modified open source software and its impact on Russian software import substitution policy. Issue 2 (April 2017) - Savelyev, Alexander
Abstract: In my previous publication, I tried to show how personal data legislation might be used for achieving the purposes of national sovereignty 1 . In this paper, I will demonstrate how open source software may be used for achieving similar purposes. However, the interplay between local copyright law, public procurement law and open source community norms creates many issues relating to the legal status and ownership in modified software, based on open source. This is especially so in the case of so-called copyleft open source licenses, where a collision occurs between copyright, as an absolute right enforceable against the world, and the copyleft provisions of license agreements, which may be treated as "rights in personam" enforceable only against the licensee. The exclusive right to derivative software as an independent object of copyright, may come into conflict with restrictions inherited from incoming copyleft licenses. This paper provides an overview and analysis of such problems faced by Russian software developers, attempting to comply with Russian import substitution provisions, by using open source components. Although it is based on Russian law, it may be applicable to other jurisdictions, since general aspects of copyright law and its interaction with private international law and contract law drive it. The paper concludes that the developer of software, containing code licensed under GPL or other copyleft provisions, receives full exclusive right to the derivative software and can commercialize it as he sees appropriate, subject only to possible claims of breach of contract rather than copyright infringement. This opens wide perspectives for using open source components regardless of the type of license used as bricks for building a de-globalized economy and society based on principles of information sovereignty.